Discovery of the South African fauna of Allophrys Förster (Hymenoptera: Ichneumonidae: Tersicochinae) - Khalaim, A. I. (Zootaxa, 2013)
Eight species of the genus Allophrys Förster are found to occur in South Africa: A. astafurovae sp. nov., A. broadi sp. nov., A. calculator sp. nov., A. dictator sp. nov., A. excavator sp. nov., A. granulata sp. nov., A. scitula sp. nov. and A. tractor sp. nov. All these species have body length 2.5–3.4 mm and fore wing length 1.7–2.3 mm, and along with members of the genus Aneuclis Förster are the smallest Afrotropical tersilochines. An identification key to eight South African species of Allophrys is provided.